Faktor-Faktor yang Mempengaruhi Penghindaran Pajak Diukur Menggunakan Rasio Keuangan - Rahimah (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of profitability, leverage, liquidity, and firm size on tax avoidance in Indonesian manufacturing companies during 2020–2024. The research employed a quantitative approach using multiple linear regression analysis on 13 sampled companies selected through purposive sampling. The research employed a quantitative approach using multiple linear regression analysis on 13 sampled companies selected through purposive sampling. The novelty of this study lies in its integrative approach, which simultaneously evaluates the impact of financial ratios on tax avoidance, proxied by the Cash Effective Tax Rate. The findings reveal that profitability, liquidity, and firm size significantly influence tax avoidance, while leverage has no effect. These results support agency theory, which highlights the conflict of interest between management and shareholders in tax strategies. The study provides practical implications for regulators to strengthen oversight of large and highly liquid firms, for investors to assess corporate governance quality, and for management to design tax avoidance strategies cautiously to avoid legal and reputational risks.